Rhino-orbital mucormycosis in a diabetes patient with renal impairment after amphotericin B deoxycholate: the role of amphotericin B lipid-complex treatment - Monteiro, Italo Gustavo Lima (2021)
Introduction: Mucormycosis is an infection caused by the ubiquitous saprophyte fungi with rapid and aggressive progression, especially in immunocompromised patients. Case report: A 57-year-old woman diagnosed with rhino-orbital mucormycosis presented with decreased renal function after treatment with amphotericin B deoxycholate which was discontinued. Renal function improved after amphotericin B lipid-complex, being also treated with itraconazole, and otorhinolaryngological surgery. Conclusion: The use of Amphotericin B deoxycholate may result in adverse effects. In this situation, Amphotericin B lipid formulation is usually the drug of choice.